Biofilm-associated Multidrug Resistant Bacteria Among Burn Wound Infections: A Cross-sectional Study - Balraj SINGH; Sonia MEHTA; Josephine ASARE-AMOAH; Peter Ofori APPIAH; Shubham CHAUHAN; Richard Donkor AMPONASH (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Introduction: Biofilm consists of an organized colony of bacterial cells that adhere to a self-produced polymeric matrix. These biofilms contribute to the pathophysiology and clinical manifestations of many illnesses, frequently leading to treatment failure. Microorganisms that produce biofilm exhibit increased resistance to antimicrobial agents compared to nonbiofilm-producing microbes. This study aimed to determine the proportion of biofilm-producing aerobic bacteria in burn wound microbiota and ascertain the percentage of multidrug-resistant (MDR) bacteria among burn wound infection-causing bacteria. Materials and Methods: This cross-sectional study was conducted at the Department of Microbiology at the Maharishi Markandeshwar Institute of Medical Science and Research Mullana, Ambala, Haryana. A total of 50 burn wound swab samples were obtained from the patients along with their detailed clinical history. The swab samples were subjected to bacterial identification employing standard microbiological methods. An antimicrobial susceptibility test was conducted for all bacterial isolates using the disk diffusion method of the modified Kirby-Bauer technique. This technique was employed using Mueller-Hinton agar plates and commercially available antimicrobial disks. The tube adherence method and the modified Congo red agar method were employed to identify biofilm-forming bacteria. Results: Of the isolates that were obtained, 56.8% were biofilm-forming bacteria. A total of 48% of the biofilm-producing bacteria were MDR. A marked resistance was noted for frequently used antibiotics like quinolones, cephalosporins, and cotrimoxazole. Staphylococcus aureus isolates were resistant to ofloxacin, penicillin G, and amikacin; Klebsiella spp. isolates were highly resistant to ampicillin, ceftazidime, trimethoprim sulfamethoxazole, tetracycline, and chloramphenicol; Pseudomonas aeruginosa isolates were highly resistant to trimethoprim sulfamethoxazole; Acinetobacter spp. isolates were resistant to cefotaxime, ceftriaxone, cefixime and trimethoprim sulfamethoxazole. For Gram-positive bacteria, Staphylococcus aureus exhibited 100% susceptibility to linezolid, vancomycin, and netilmycin while coagulase-negative Staphylococci isolates were sensitive to all antibiotics. Klebsiella, Proteus, Pseudomonas aeruginosa, and Acinetobacter spp. exhibited the highest sensitivity to carbapenem antibiotics among Gram-negative bacteria. Conclusion: The study highlights the rising prevalence of MDR bacteria in burn wound infections and the necesssity of effective infection control measures and treatment methods to combat these biofilm-forming MDR bacteria.